Optimizing the Utilization of Package Books during the Covid-19 Pandemic: (Strategy of Islamic Religious Education Teachers in Junior High Schools) - Kartini, Kartini; Efendi, Erwatul (Jurnal Konsepsi, 2024)
This study discusses optimizing the use of textbooks during the covid 19 pandemic. The main discussion in this study is the use of textbooks at SMPN 1 Makassar during the covid 19 period; what is the strategy of PAI teachers at SMPN 1 Makassar in optimizing the use of Islamic religious education textbooks during the covid period. 19 at SMPN 1 Makassar. This study aims to: determine the use of textbooks at SMPN 1 Makassar during the covid 19 pandemic; knowing the strategies of SMPN 1 Makassar teachers in optimizing the use of PAI textbooks; knowing the obstacles and solutions in optimizing the use of textbooks during the covid 19 pandemic at SMPN 1 Makassar. This research uses descriptive qualitative research. This research uses a pedagogical, sociological, and grounded research approach. The author uses data collection techniques, including observation by making direct observations at the location to be studied; interviews by interviewing the principal, 3 PAI study teachers, library staff, curriculum teachers, and students at the research site; and documentation, where the researcher takes documents or files from the location researcher and triangulation, in the validity of the data the researcher uses technical triangulation and source triangulation, data analysis uses data reduction, data presentation, and conclusion drawing. The results showed that PAI textbooks at SMPN 1 Makassar ran as much as possible with various teaching strategies being carried out